MHC class II molecules and tumour immunotherapy - Oven, Irena (Radiology and oncology (Ljubljana), 2005)
Tumour immunontherapy attempts to use the specificity and capability of the immune system to kill malignant cells with a minimum damage to normal tissue.n Increasing knowledge of the identity of tumour antigens should help us design more effective therapeutic vaccines. Increasing evidence has demonstrated that MHC class II molecules and CD4+T cells play important roles in generating and maintaining antitumour immune responses in animal models. These data suggest that be necessary to involve both CD+ and CD+T cells for more effective antitumour therapy. Novel strategies have been developed for enhancing T cell responses against cancer by prolonging antigen prersentation of denritic cells to T cells, by the inclusion of MHC class II-restricted tumour antigens and by genetically modifying tumour cells to present antigen to T lymphocytes directly. Vaccines against cancers aim to induce tumour-specific effector T cells that can reduce tumour mass and induce development of tumour-specific T cell memory, that can control tumour relapse.
Keywords: imunoterapija; onkologija; rak (medicina); tumorji